Isolated psoas schwannoma: A rare retroperitoneal tumor - Mohd Ilyas; Zubair Ahmad; Irshad Ahmad Banday; Suhail Rafiq; Naseer Choh (Acta Medica International, 2018)
Retroperitoneal neurogenic tumors are very rare. Isolated or primary psoas schwannoma is one of the rarest tumors of retroperitoneum. The images of such a case are presented in this report.